Comparison of the effect of early versus late surgical strategies on outcomes in patients with hand enchondromas complicated with pathological fractures - Akgün, Erkan; Çevik, Hüseyin Bilgehan (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2025)
This study aimed to evaluate the advantages and disadvantages of early versus delayed single-stage surgery in patients with hand enchondromas who developed pathological fractures, focusing on local tumor control and hand function, to determine the optimal timing for surgery. Delayed surgical curettage may offer advantages regarding both local tumor control and hand function outcomes.Thirty-five patients who developed pathological fractures due to solitary hand enchondromas and underwent surgical treatment between 2015 and 2021 were analysed. Patients were divided into two groups based on the timing of surgery. Patients who underwent surgical treatment immediately after a pathological fracture were assigned to the early-surgery group, and those who underwent surgical treatment after waiting for fracture union were assigned to the late-surgery group. Demographic data, lesion characteristics, and fixation methods were analysed. Parameters affecting outcome measurements were analysed, including visual pain scale, fracture healing time, recurrence, ROM, time to return to daily activities, and secondary surgical procedures.The study included 35 patients, of whom 24 were female, with a median age of 33 years. Fifteen patients were included in the early-surgery group and 20 in the late-surgery group, with a follow-up period of 36.3 and 38.9 months, respectively. The duration of surgery, time to fracture union, and total physical therapy duration during treatment were lower in the late-surgery group (p<0.05). At the final follow-up, the mean loss of ROM was 17.6˚ in the early-surgery group and 3.3˚ in the late-surgery group (p=0.00). The rate of secondary surgery was higher in the early-surgery group (p=0.040).In patients with hand enchondromas presenting with pathological fractures, early surgery resulted in higher complication rates, poorer functional outcomes, and an increased need for secondary surgeries.
Keywords: hand; enchondroma; pathological fracture; surgical timing